Gen z confiding: the role of anonymity and loneliness in the self-disclosure among chatgpt users - Shepia, Dinda Rahma; Rohayati, Nita; Ibad, Choirul (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2025)
This study aims to determine the effect of anonymity and loneliness on self-disclosure. This study employs quantitative research techniques and a causal-based research design. The research respondents are Generation Z users of ChatGPT as a medium for confiding, with a total of 204 respondents determined using the Cohen formula. Data were collected using a Likert-based psychological scale distributed through Google Forms. The instruments used included the Revised Self- Disclosure Scale, Perceived Anonymity Scale, and UCLA Loneliness Scale. Data processing techniques in this study consist of a normality test, a linearity test, and a multiple linear regression test, with data processing conducted using SPSS version 26,0 for Windows. The results showed that anonymity had a significant effect on self-disclosure among Gen Z ChatGPT users (p = 0,009). In addition, loneliness also had a significant relationship with self-disclosure (p = 0,000). Simultaneously, both variables significantly influenced self-disclosure (p = 0,000). The higher the sense of anonymity and loneliness felt by an individual, the greater their tendency to be open in expressing themselves.